Legal protection of the environment: A comparative law study - Nadia Hamouti; Safae El bakouhi (Journal of Environment and Sustainability Education, 2025)
The environment is one of the values that the legislator seeks to protect and preserve, as it has granted it protection that is one of the most striking manifestations of the legal protection of the environment. This is due to the injunctive effect of sanctions through the extension of the rule of law via the judiciary. Each country, within the framework of its territorial sovereignty, has enacted laws and regulations to protect the environment and combat pollution, while accompanying this legislation with sanctions that force offenders to comply, because there is no point in enacting legislation designed to protect the environment if it is not accompanied by a sanction that deters the offender and restores the situation to what it was before. The results achieved include the strengthening of legal frameworks, progress in international law, varying degrees of effectiveness in the application of laws and the involvement of citizens in environmental justice.